Converting the cigarette butts into valuable products using the pyrolysis process - M. Hazbehiean; N. Mokhtarian; A. Hallajisani (Global Journal of Environmental Science and Management)
More than 5.5 trillion cigarettes are manufactured, and approximately 4.5 trillion cigarette butts are being scattered across the globe per year. These cigarette butts are considered as one of the most hazardous wastes and environmental threats in the world. Thermochemical techniques can be used to turn biomass and solid wastes into valuable final products. Pyrolysis is a comfortable thermochemical technique for turning biomass into biochars, biofuels, briquette solid fuels, and further valuable products such as activated carbons, carbon black, and printing ink. In this study, it was attempted to review the available researches about pyrolysis of cigarette butts with an emphasis on transforming them into carbonated solid and liquid products. It was found that, in addition to the process variables, the type of cigarette butts treatment has a significant effect on the yield and quality of the finished goods. Further studies on the pyrolysis of cigarette butts, especially microwave-assisted pyrolysis and hybrid waste pyrolysis, seemed to be necessary. Solving the technical issues associated with the pyrolysis of cigarette butts to produce the value-added goods would contribute to their application in waste disposal and recycling of other resources. Future studies should focus on the separation methods with the help of gas products to provide the heat required in the reactor. Moreover, mixing the sewage sludge material, as a feed, with cigarette butts and application of appropriate models and experiments to attain the products with specific properties  are recommended. The results of this study can be used to eliminate the hazards of the cigarette butts scattered in the environment and create the added value for the pyrolysis process.